Gender-Specific Related Factors for Suicidal Ideation During COVID-19 Pandemic Lockdown Among 5,175 Chinese Adolescents - Zhu, Jin; Li, Baohua; Hao, Fengcheng; Luo, Linlin; Yue, Song; Zhai, Jinguo; Chen, Min; Liu, Yan; Liu, Debiao; Wang, JianLi (Frontiers in Public Health, 2022)
Background Suicide was an urgent issue during pandemic period in adolescents. However, few studies were focused on suicide during COVID-19 pandemic lockdown. Methods An online survey was conducted among 5175 Chinese adolescents from June 9th to 29th in 2020 to investigate the prevalence of suicidal ideation (SI) during COVID-19 pandemic lockdown. Gender-specific stepwise logistic regression model was used. All analyses were performed with STATA 15.0. Results 3.00% of the participants had reported to have SI during the COVID-19 pandemic lockdown period. The prevalence of female SI (3.64%, 95% CI: 2.97%- 4.45%) was higher than that of males (2.39%, 95% CI: 1.88%- 3.05%) (2= 6.87, p=0.009). Quarreling with parents (OR=9.73, 95% CI: 5.38- 17.59), insomnia (OR=5.28, 95% CI: 2.81- 9.93), previous suicide attempt history (OR=3.68, 95% CI: 1.69- 8.03), previous SI history (OR=2.81, 95% CI: 1.30- 6.06) and feeling depressed during pandemic lockdown (OR=2.26, 95% CI: 1.22- 4.18) were positively associated with the males’ SI. However, emptiness inside (OR=4.39, 95% CI: 2.19- 8.79), quarreling with parents (OR=3.72, 95% CI: 2.16- 6.41), insomnia (OR=3.28, 95% CI: 1.85- 5.80), feeling anxious (OR=2.62, 95% CI: 1.46- 4.70) and father emotional warmth (OR=0.38, 0.20- 0.72) were associated with females’ SI mostly. Conclusions Female adolescents with emptiness from mal-family were at much higher risk of having SI during COVID-19 lockdown. We have to specify suicide prevention policy and interventions for adolescents in the pandemic crisis based on gender gaps.